Machiavellianism, Impulsivity, and Empathy: Understanding Aggressive Driving Behavior - Rendy Alfiannoor Achmad; Silvia Kristanti Tri Febriana; Laily Maulida; Igha Ananda Saidah Muharram; Lili Aprilianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2023)
This study aimed to investigate the impact of impulsivity, Machiavellianism, and empathy on the inclination towards aggressive driving behavior. A cross-sectional analysis was conducted, utilizing a sample size of 315 Indonesian drivers. Accordingly, the instruments used include Aggressive Driving Behavior Scale (ADBS), Short Version of the UPPS-P (SUPPS-P) Scale, Machiavellian Personality Scale (MPS) and Interpersonal Reactivity Index (IRI) Scale. The multiple linear regression results showed that impulsivity, Machiavellianism, and empathy significantly influenced the tendency toward aggressive driving behavior with F count of 12.454 and significance level of .000 < .05. Furthermore, the dimensions of impulsivity, lack of perseverance, and Machiavellianism, were observed to partially have an effect on the tendency toward aggressive driving behavior at .221 or 22.1%, which was categorized as moderate. It was also important to acknowledge that the other dimensions observed in this study had no significant effect on the subject matter.